(untitled) - Schmiechen, Peter (U.S.A, 2005)
Jesus' death and resurrection are undeniably central to the Christian faith. But how, precisely, is their significance to be understood? Concerned to reinvigorate the church's teaching on the cross, the resurrection, and salvation - the atonement - Peter Schmiechen here invites readers to rediscover the wealth of the Christian tradition. In Saving Power he makes ample use of primary sources to unpack ten distinct theories of atonement, welcoming aspects of each rather than championing only one. Along the way, he demonstrates that while most Christians assume the basic theme of atonement to be sin and forgiveness, other powerful themes - liberation from oppressive powers, reconciliation in the face of division, and the hope of resurrection in the face of death, for instance - also deserve to be studied and preached. Affirming orthodox teaching while offering a positive take on marginal views, Saving Power is a crucial resource for anyone who seeks a fuller understanding of Christ's work.
Keywords: Church